Competitive Value When Only Labor is Scarce - Bishop, Robert L. (Quarterly Journal of Economics, 1985)
Even when only labor is scarce, the validity of a labor theory of value depends on reducing all labor to a homogeneous equivalent. The various implicit or explicit efforts of Smith, Ricardo, and Marx to do so are shown to fail on more counts than previously recognized. The labor theory is also shown to fail when laborers are not indifferent among alternative occupations.